Saints and the Audience in Middle English Biblical Drama - Scoville, Chester N. (Chester Norman), 1968- (Book collections on Project MUSE., 2004)
"The study of saints in medieval biblical drama has often been neglected in favour of the study of sinners - the villains and the rogues. In Saints and the Audience in Middle English Biblical Drama, Chester N. Scoville takes a different tack, examining the language and rhetoric of saintly characters in Middle English biblical plays. Scoville contends that the plays focus attention on the interaction between the divine realm and the human realm, that the saintly characters are key to seeing this interaction, and that the overall function of the plays is to instill in the audience a shared point of view defined both by doctrine and by experience."--Jacket.